2019
DOI: 10.1177/0963693519885386
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and numerical investigation into brush seal hysteresis without pressure differential

Abstract: Brush seal is a novel type contact seal, and it is well-known due to its excellent performance. However, there are many intrinsic drawbacks, such as hysteresis, which need to be solved. This article focused on modeling hysteresis in both numerical way and analytic way without pressure differential. The numerical simulation was solved by the finite element method. General contact method was used to model the inter-bristle contact, bristle-rotor contact, and bristle-backplate contact. Bristle deformation caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Further verification/validation works have been routinely carried out during the development of the numerical method. Extra comparisons have been made against experimental data provided by Demiroglu et al [5] and Duran et al [14,15] as well as against other researchers' models such as those by Stango et al [6,7] and Kang et al [27]. Validations for pressurized seals are particularly difficult due to scarce experimental data available in the public domain.…”
Section: Baseline Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Further verification/validation works have been routinely carried out during the development of the numerical method. Extra comparisons have been made against experimental data provided by Demiroglu et al [5] and Duran et al [14,15] as well as against other researchers' models such as those by Stango et al [6,7] and Kang et al [27]. Validations for pressurized seals are particularly difficult due to scarce experimental data available in the public domain.…”
Section: Baseline Validationmentioning
confidence: 99%
“…Hysteresis ratio has typically been adopted for classical mechanic studies regarding friction (for example see Israelachvili et al [29]). Kang et al [27] has also adopted this metric to investigate the hysteresis performance of brush seals.…”
Section: Figurementioning
confidence: 99%
“…In solid mechanics, the approximate differential equation for the deflection curve is [18][19][20][21] :…”
Section: Theoretical Verificationmentioning
confidence: 99%
“…Duran et al [15,16] and Zhang [17] established a 3D calculation model of multiple bristles and simulated numerically their deformation and the contact force between them and the rotor during the loading and unloading cycle of the radial offset of the rotor. Kang et al [18] found that the lay angle of the bristles had a greater effect on the HE when the pressure difference was not considered. However, once separated, there is no contact force between the bristles and the rotor, and the deformed bristles can continue to recover; therefore, the contact force is no longer applicable for describing the deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Duran et al[15,16] and Zhang[17] established a 3D calculation model of multiple bristles and simulated numerically their deformation and the contact force between them and the rotor during the loading and unloading cycle of the radial offset of the rotor. Kang et al[18] found that the lay angle of the bristles had a greater effect on the HE when the…”
mentioning
confidence: 99%